Emotions' influence on customers’ e-banking satisfaction evaluation in e-service failure and e-service recovery circumstances - Nyagadza, Brighton; Mazuruse, Gideon; Muposhi, Asphat; Chuchu, Tinashe; Makoni, Tendai; Kusotera, Brain (Elsevier, 2022)
Purpose